1997
DOI: 10.2169/internalmedicine.36.333
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral Muscular Dystrophy: Clinical Diversity and Genetic Abnormalities in Japanese Patients.

Abstract: We studied 71 Japanese individuals, 42 patients (30 familial and 12 sporadic) suspected to have facioscapulohumeral muscular dystrophy (FSHD) and 29 family members, clinically and genetically using the chromosome4qter DNAmarker pl3E-ll. Early onset FSHDwas detected in 7patients, tortuosity of retinal arterioles and hearing impairment in 3 patients, progressive respiratory failure in 3 patients and limb-girdle type muscular weakness in 6 patients. Thirty-six (85.7%) FSHDpatients, 3 asymptomatic family members a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…28 That said, there is a subgroup of patients, typically with the largest contractions and earliest onset of disease, who require hearing aids. 29,30 The patient-reported risk of extramuscular manifestations of FSHD seen here was also infrequent and did not track with D4Z4 contraction size, with the exception of hearing aid use, which was higher in participants with contractions 18kb. However participants may underreport extramuscular manisfestations, as they may be asymptomatic or slightly symptomatic, and they may not consult a physician to have these manifestations diagnosed.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…28 That said, there is a subgroup of patients, typically with the largest contractions and earliest onset of disease, who require hearing aids. 29,30 The patient-reported risk of extramuscular manifestations of FSHD seen here was also infrequent and did not track with D4Z4 contraction size, with the exception of hearing aid use, which was higher in participants with contractions 18kb. However participants may underreport extramuscular manisfestations, as they may be asymptomatic or slightly symptomatic, and they may not consult a physician to have these manifestations diagnosed.…”
Section: Discussionmentioning
confidence: 66%
“…One study suggested the level of hearing impairment is no greater than what would be expected for age . That said, there is a subgroup of patients, typically with the largest contractions and earliest onset of disease, who require hearing aids …”
Section: Discussionmentioning
confidence: 99%
“…Retinal arteriolar tortuosity has also been exceptionally reported in facio-scapulo-humeral dystrophy (FSHD), an autosomal-dominant muscular disorder characterized by proximal muscle weakness, amyotrophia, and contractures [23,24]. Linkage with the FSHD locus (4q35ter) was excluded in our family.…”
Section: Discussionmentioning
confidence: 93%
“…While myofiber atrophy due to denervation/renervation generally involves “grouped” angular-shape atrophic fibers, atrophic myofibers with a myogenic cause tend to be scattered (Banker, 1986; Benedetti et al, 2005). The angular myofibers in FSHD were proposed to be due to a myogenic cause due to their scattered distribution (Engel and Kossman, 1963; Lin and Nonaka, 1991; Nakagawa et al, 1997). We observed the same scattered distribution of angular-shaped myofibers in the Pitx1 transgenic mice muscles.…”
Section: Discussionmentioning
confidence: 99%